APPLICATION OF THE PRECAUTIONARY PRINCIPLE IN THE LEGALIZATION OF A DEED UNDER THE HAND BY A NOTARY IN ORDER TO INCREASE LEGAL CERTAINTY - Putra, Gerry Akbarhananta (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2024)
Notaries have the authority to make authentic deeds, apart from that, notaries also have other authorities, including legalization. In practice, notaries exercise their authority to carry out legalization, there is still a discrepancy between regulations and implementation which is caused by the minimal and asynchronous various legal arrangements regarding legalization, thus causing a lack of legal certainty regarding the notary's authority to carry out legalization. So this research discusses how to apply the precautionary principle and the legal consequences if a notary ignores the precautionary principle against a notary's authority in carrying out legalization. The purpose of this research is to analyze the application of the precautionary principle. This study uses a normative juridical approach and uses secondary data. The results of this study are that the Notary is obliged to apply the precautionary principle by Recognizing the Identity of the Appearing Person, carefully reading the Deed to be Legalized, fulfilling Legalization techniques, and keeping records of the legalization process. The notary also needs to ensure that the parties understand the essence and legal consequences of the deed legalized by him. As for the legal consequences if the notary ignores the precautionary principle, namely the deed that is being legalized can be declared null and void by law or can be canceled which is stated by the court. The notary can also be sued for legal action by the injured party in the form of a lawsuit through the court and submit a report to the Regional Supervisory Board so that the notary concerned is subject to administrative sanctions.Keywords: Prudence, Legalization, Underhand Deed, Notary, dan Legal Certainty